Post-Operative Pain in Transabdominal Preperitoneal (TAPP) Hernia Repair: Mesh Fixation with Tacks Versus Non-Fixation - Saad Ali Shah, Raheel Imam Qureshi, Javaid Sajjad Hashmi, Muhammad Tariq Khan, Muhammad Hanif Memon, Abdul Rasheed Zai (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the post-operative pain in transabdominal preperitoneal (TAPP) hernia repair: Mesh fixation with tacks versus non fixation. Study Design: Comparative study Place and Duration of Study: Department of Surgery Unit B, Mardan Medical Complex, Mardan from 1st October 2019 to 30th September 2021. Methodology: One hundred participants who were admitted for inguinal hernia repair through laparoscopic surgical procedure were enrolled as study participants and divided into two groups. General anesthesia was administered to all patients and a carbon dioxide pressure of 14mmHg was used for keeping pneumo-peritoneum during the surgical procedure. An incision in peritoneum was made post identification of herniasac. Pain index was measured by Visual Analogue Scale at day 1, day 3, day 7 and day 14 followed by one and six months post-surgery. Results: The mean age of group A and group B patients in the present study were 51.2±9.5 and 52.1±9.7 years respectively with majority being males in both groups. Majority of patients in both group had unilateral herni. Group B had shorter surgery duration with lessen hospital stay however chances of recurrence as 12% and wound infection as 6% was higher in it respectively. The post operative pain was 65±9.3 and 66±9.1 in group A and B. Conclusion: Mesh fixation is a longer duration process requiring longer hospital stay, however it provides less chances of complications as wound infection and recurrence. There was no difference in post operative pain in both groups.